Instants Spirituality: Analysing The Phenomenon of Practical Prayers and Deeds on Social Media - Oktafiani, Tri Utami; Wawaysadhya, Wawaysadhya; Chair, Badrul Munir (Aqlam: Journal of Islam and Plurality, 2025)
In recent years, the transformative influence of Social Media on religious practices has been profound. A notable phenomenon is the emergence of Social Media accounts with millions of followers, offering guidance on prayers and daily deeds for specific intentions. This research will examine the phenomenon of seeking prayers on Social Media for instant and practical purposes using Jean Baudrillard's theory of Simulacra and Hyperreality. The aim of this research is to understand the impact of seeking and practicing prayers and religious acts on social media by exploring content related to that and the responses of followers to such content. This research is qualitative in nature, using a phenomenological approach. Data was collected from three influential TikTok accounts: Irfan Rizki, Meliza Arnelia, and Ajie Pangestu, known for their large following and engaging content on religious practices. The results show that there are two types of responses from netizens' comments regarding the prayers and deeds on the content: the first group reports success and positive outcomes after practicing certain prayers and religious acts; the second group responds by stating that they did not experience the expected changes even though they practiced as advised. The analysis concludes that the content of such practical prayers and deeds on social media operates in a similar purpose with advertisements containing hyperreal signs to attract audience attention. The group that successfully practices a certain prayer or religious act provides testimonials about their success, thus creating a perspective that these prayers and deeds are merely products that can be applied practically and have an immediate impact. The effect of this viewpoint is the emergence of instant spirituality, placing religion in a reciprocal relationship. Meanwhile, the group that fails to achieve instant effects from the prayers and rituals tends to consider the prayers useless. Key Words : Prayers, instants spirituality, hyperreality, simulacra, social mediaAbstrak: Kehadiran media sosial telah mengubah pola keberagamaan masyarakat dalam beberapa tahun terakhir. Salah satu fenomena yang muncul adalah maraknya akun media sosial dengan jutaan follower yang menyajikan konten doa-doa dan amalan- amalan praktis untuk berbagai tujuan tertentu. Penelitian ini akan mengkaji fenomena pencarian doa-doa di media sosial untuk tujuan instan dan praktis dengan menggunakan teori Simulakra dan Hiperrealitas Jean Baudrillard. Penelitian ini bertujuan untuk mengetahui dampak pencarian dan pengalaman doa-doa dan amalan-amalan praktis di media sosial dengan menelusuri isi konten yang terkait dengan doa-doa praktis dan respon para follower atas konten-konten tersebut. Penelitian ini merupakan jenis penelitian kualitatif dengan pendekatan fenomenologi. Data penelitian dikumpulkan dari tiga akun media sosial TikTok yaitu Irfan Rizki, Meliza Arnelia, dan Ajie Pangestu. Hasil dari penelitian menunjukkan bahwa terdapat dua macam respon dari komentar- komentar netizen atas konten tersebut, yaitu: kelompok pertama, yang membuktikan keberhasilan dan kesuksesan setelah mengamalkan doa-doa tertentu; dan kedua, kelompok yang merespon dengan menceritakan tidak adanya perubahan yang diharapkan setelah mengamalkan doa-doa tersebut. Hasil analisis dari penelitian ini menyimpulkan bahwa konten doa-doa praktis di media sosial memiliki peran serupa iklan yang mengandung hiperrealitas penandaan untuk menarik perhatian audiens. Kelompok yang berhasil mengamalkan suatu doa atau amalan tertentu memberikan testimoni tentang keberhasilan mereka sehingga memunculkan suatu sudut pandang bahwa amalan-amalan dan doa-doa adalah seperti produk yang dapat diaplikasikan secara praktis dan langsung berdampak secara instan. Dampak dari pandangan tersebut adalah munculnya spiritualitas instan dan menempatkan agama sebagai hubungan timbal-balik. Sementara kelompok yang merasakan kegagalan dalam memperoleh dampak instan dari doa-doa dan amalan-amalan tersebut cenderung beranggapan bahwa doa itu tidak berguna. Kata Kunci : Doa, spiritualitas instan, hiperrealitas, simulakra, media sosial